Pemanfaatan Tempurung Kelapa Sebagai Bahan Baku Arang Aktif dan Aplikasinya Untuk Penjernihan Air Sumur di Desa Belor Kecamatan Ngaringan Kabupaten Grobogan - Suhartana, Suhartana (BERKALA FISIKA, 2006)
Waste Piece of Coconut shell used in society often only used upon which burn or firewood. Some furniture industries minimize there, exploited as a tool of physic educative and souvenir. In other hand, can be taken away from piece of coconut shell could to raw material of active charcoal. Chemical content of active charcoals is carbon compound, is very good for process of liquid material purification, inorganic and also organic material goodness. In this research is existing active charcoal, used to make clear ground water at Belor Ngaringan Grobogan District. Result after treatment by active charcoal pH, hardness, salinity, biologycal oxygen demand and chemical oxygen demand were decrease. Â  Keyword: piece of coconut shell, active charcoal, liquid material purification.